“Artificial Intelligence and Its Influence on Human Resource Practices in the IT Industry.” (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Research case "A Study on AI Impact towards Human Resource with Reference to IT Company" examines how artificial intelligence (AI) is revolutionizing the Human Resource Management (HR) industry, with a particular emphasis on the tactics and contributions of IT Company, a world leader in technology and consulting services. This Study explores the revolutionary potential and related constraints of artificial intelligence's role in HR. In particular, it encompasses difficulties such as operational challenges in integrating AI into legacy HR, ethical and regulatory considerations related to AI, data privacy concern, ethical & legal issues and automation task and enabling data driven decision-making across various HR functions concerns resulting from reliance on massive datasets. The results are intended to provide light on how artificial intelligence (AI) might further disrupt the various HR sector and the strategic role IT Company plays in influencing this change and benefiting the sector. What an artificial intelligence (AI) is revolutionizing the Human Resource Management (HR) industry, with a particular emphasis on the tactics and contributions of IT Company, a world leader in technology and consulting services. This Study explores the revolutionary potential and related constraints of artificial intelligence's role in HR. In particular, it encompasses difficulties such as operational challenges in integrating AI into legacy HR, ethical and regulatory considerations related to AI, and automation task and enabling data driven decision- making across various HR functions.